Effects of chromium content on fatigue crack growth behavior of Ti-48Al-xCR alloys - Tamin, Mohd. Nasir; Hamzah, Esah; Ong, Wei Rex (2008)
Gamma TiAl alloys are candidate materials for aircraft structural applications due to their inherent high specific stiffness and strength. However, limited room-temperature ductility of these alloys calls for investigation on fatigue crack growth resistance. In this respect, a series of fatigue crack growth tests are conducted on precracked M(T) specimens at constant load ratio of minimum to maximum stress, R = 0.1. All tests are performed at room temperature for baseline fatigue crack growth behavior. Effects of different chromium content on fatigue crack growth rates, da/dN and threshold stress intensity factor ranges, ΔKth for Ti-48Al-xCr alloys (x = 0, 2, 4 and 8 at. %) are examined. Results show that fatigue crack growth behavior of these alloys displays a threshold growth stage followed by a power-law growth behavior until final fracture of the sample. The threshold ΔKth ranges from 11 MPa√m for Ti-48Al to the lowest magnitude of 4.5 MPa√m for Ti-48Al-8Cr alloy. In the Parislaw crack growth region, da/dN ranges between 10-4 to 10-2 mm/cycle while the crack-tip driving force, ΔK varies from 11 to 35 MPa√m, respectively. The magnitude of ΔK at final fracture for Ti-48Al-xCr (x = 0, 2, 4 at. %) is about 34 MPa√m which approximate the fracture toughness of the alloys. Fracture toughness of Ti-48Al- 8Cr alloy is much lower at 18 MPa√m. Threshold ΔKth is linearly correlated with microstructure features of lamellar grain size and lath spacing. Dominant fatigue fracture mechanisms observed are crack deflection, stepped crack growth and formation of shear ligaments. These mechanisms are responsible for the observed torturous crack path and collectively improved crack growth resistance of Ti-48Al-xCr alloys.